Pengaruh Jiwa Kewirausahaan Pengurus dan Kualitas Pelayanan Terhadap Partisipasi Anggota serta Implikasinya Terhadap Perkembangan Usaha Koperasi Konsumen di Kota Bandung - Tri Agustina; Indra Fahmi; Deddy Supriyadi (LPPM Universitas Koperasi Indonesia, 2026)
Consumer cooperatives in Bandung City are expected to serve as strategic institutions in supporting the local economy. However, their business development has tended to stagnate and has not yet made a significant contribution to the Gross Regional Domestic Product (GRDP). This study aims to examine the influence of managerial entrepreneurial spirit and service quality on member participation and its implications for cooperative business development. The research employs a quantitative approach with a causal-confirmatory design. Primary data were collected using a questionnaire instrument with a Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0.9.9 software. The findings indicate that, simultaneously, managerial entrepreneurial spirit and service quality influence member participation by 55%. Furthermore, managerial entrepreneurial spirit, service quality, and member participation together affect cooperative business development by 29.1%, with the remaining variance explained by other factors. Partially, only service quality was found to have a positive and significant effect on member participation.